LITHOSPHERIC STRUCTURE AND TECTONIC EVOLUTION OF INTRACRATONIC BASINS: THE CONGO BASIN A NATURAL LABORATORY - MADDALONI, FRANCESCA (Università degli Studi di Trieste, 2021)
The aim of this thesis is to identify the tectonic processes that lead to the long-term topography variations of the cratonic areas that contain the memory of the past deformation. These areas are the intracratonic basins (ICBs), which are usually very large basins, characterized by long-term subsidence. Among them, the Congo Basin (CB) occupies a large part of the Congo Craton, derived from the amalgamation of different cratonic pieces. The CB is a typical intracratonic basin, due its slow and long-lived subsidence history and the largely unknown formation mechanisms. It recorded the history of deposition of up to one billion years of sediments, above a metamorphic basement, one of the longest geological records on Earth. Thus, it can be considered a natural laboratory, suitable to achieve the objectives of my thesis project. To improve our knowledge on the interplay between shallow and deep tectonic processes, which lead to the formation of the CB, I first reconstructed the stratigraphy and depths of the main seismic horizons of the basin, using geological and exploration geophysical data. The results revealed that the CB formed very probably as a failed rift in late Mesoproterozoic (about 1200 Myr) and evolved during the Neoproterozoic and Phanerozoic, under the influence of far-field compressional tectonic events, global climate fluctuations, between icehouse and greenhouse conditions, and drifting of Central Africa through the South Pole towards its present-day equatorial position. These events caused the migration over time of the sedimentary depocenters within the central part of the basin (Cuvette Centrale). Afterwards, I analyzed gravity data, using the seismic data and density of sedimentary samples as constraints, in order to investigate the shallow crustal structure of the basin. The results lead to the identification of the continuity of the NW-SE oriented tectonic structures and of small basins in areas uncovered by seismic data. From the analysis of the gravity anomalies, I could further ...